2011
DOI: 10.1093/toxsci/kfr252
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine CCL2 Protects Against Methylmercury Neurotoxicity

Abstract: Industrial pollution due to heavy metals such as mercury is a major concern for the environment and public health. Mercury, in particular methylmercury (MeHg), primarily affects brain development and neuronal activity, resulting in neurotoxic effects. Because chemokines can modulate brain functions and are involved in neuroinflammatory and neurodegenerative diseases, we tested the possibility that the neurotoxic effect of MeHg may interfere with the chemokine CCL2. We have used an original protocol in young mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Recent- ly, Godefroy et al (2012) reported that CCL2 functions defensively against methylmercury toxicity, although the underlying molecular mechanism is unknown. In future research, the detailed mechanisms underlying methylmercury induction of NF-κB activation and chemokine expression will be further explored, and perhaps reveal a novel mechanism of methylmercury neurotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Recent- ly, Godefroy et al (2012) reported that CCL2 functions defensively against methylmercury toxicity, although the underlying molecular mechanism is unknown. In future research, the detailed mechanisms underlying methylmercury induction of NF-κB activation and chemokine expression will be further explored, and perhaps reveal a novel mechanism of methylmercury neurotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an elevation of MCP-1 expression in response to MeHg exposure was observed in mice experiment (10 mg/kg/day for 7 days) [22] and human 1321N1 astrocytoma cells (10 μM for 6 h) [26]. It was also reported to work as an alert system for MeHg exposure, using MCP-1-knockout mice [18].…”
Section: Introductionmentioning
confidence: 99%
“…Cytokines play an important role in intercellular signaling, and over 100 types have been described, including tumor necrosis factor (TNF), transforming growth factor (TGF), interleukins, interferons, and chemokines1415. Recently, Rostene et al 16. reported the relationship between CCL2, a chemokine, and methylmercury toxicity.…”
mentioning
confidence: 99%